Reader's guide to critical appraisal of cohort studies: 2. Assessing potential for confounding - Mamdani, Muhammad (BMJ Publishing Group Ltd., 2005)
Although confounding is an important problem of cohort studies, its effects can be minimised to enable valid comparison